Public Relations Strategy of PT Jasamarga Pandaan Tol in Establishing Relationships with External Stakeholders - Sulkha, Auzi Trisiyas; Sinduwiatmo, Kukuh (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the PR strategy of PT Jasamarga Pandaan Tol in establishing relationships with external stakeholders. This study used descriptive qualitative method. The object of this research is the Public Relations of PT Jasamarga Pandaan Tol. The process of data collection was carried out by means of observation, in-depth interviews and documentation. The results of the study show that (1) the strategy adopted by Public Relations of PT Jasamarga Pandaan Tol is to establish good relations through community leaders and local village governments to control community opinions so that there are no conflicts. (2) Another strategy used by Public Relations of PT Jasamarga Pandaan Tol is through an interaction approach by developing a Social and Environmental Responsibility program as problem solving.